Morphology and distribution of Catenula adhaerens Mereschkowsky (Bacillariophyceae) in southern Brazil - Garcia, Marinês (2011)
The morphology and distribution of Catenula adhaerens Mereschkowsky was studied from 24 beaches in southern Brazil. The study was based on observation of 214 samples from superfi cial sediments of sandy beaches from the states of Rio Grande do Sul and Santa Catarina. The morphological variability observed in Brazilian specimens was similar to those described in literature, except for the stauro that was absent in some valves. Catenula adhaerens presented a wide distribution, occurring in exposed, dissipative and refl ective sandy beaches. However, it occurred with most relative frequency (22%) in estuarine beaches. The species was not observed in the open, exposed and dissipative sandy beaches. This absence might be related to the beach hydrodynamic, sand grain size, shape and superfi cial texture limiting the Catenula adhaerens distribution in southern Brazil.